2014
DOI: 10.2106/jbjs.m.00895
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Determinants of Sacral Dysmorphism and Implications for Safe Iliosacral Screw Placement

Abstract: Background: Upper sacral segment dysplasia increases the risk of cortical perforation during iliosacral screw insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
117
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 34 publications
5
117
3
Order By: Relevance
“…With wider use of screw fixations in different positions in the posterior pelvic ring (iliosacral or transsacral), several morphologic variations were described and the terms ''dysplastic sacrum'' and ''sacral dysmorphism'' were introduced, however, there is lack of consensus regarding their definitions [2,4,7,22,29]. Routt et al [29] described five qualitative radiographic signs for sacral dysplasia based on pelvic-outlet and true lateral views, whereas quantitative parameters were described by others [17,22]. Kaiser et al [17] developed a sacral dysmorphic score based on coronal and axial angulation of the upper sacral segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With wider use of screw fixations in different positions in the posterior pelvic ring (iliosacral or transsacral), several morphologic variations were described and the terms ''dysplastic sacrum'' and ''sacral dysmorphism'' were introduced, however, there is lack of consensus regarding their definitions [2,4,7,22,29]. Routt et al [29] described five qualitative radiographic signs for sacral dysplasia based on pelvic-outlet and true lateral views, whereas quantitative parameters were described by others [17,22]. Kaiser et al [17] developed a sacral dysmorphic score based on coronal and axial angulation of the upper sacral segment.…”
Section: Discussionmentioning
confidence: 99%
“…Routt et al [29] described five qualitative radiographic signs for sacral dysplasia based on pelvic-outlet and true lateral views, whereas quantitative parameters were described by others [17,22]. Kaiser et al [17] developed a sacral dysmorphic score based on coronal and axial angulation of the upper sacral segment. Mendel et al [22] reported the lateral sacral triangle configuration in the lateral view.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all signs were also found in their non‐dysmorphic cluster, but with lower prevalence of 14–46%. Interestingly, the Kappa values for the interobserver reliability range between 0.36–0.59 (fair to moderate according to Landis & Koch) . Both topics were not addressed in our study.…”
Section: Discussionmentioning
confidence: 68%
“…The awareness of anatomical variations in the posterior pelvic ring in recent years is based on the complications of percutaneous screw fixation use. No common definition (“dysplastic sacrum,” “sacral dysmorphism,” or “upper sacral segment dysplasia”) and standardized determination of these variations is present in the literature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation